REPRODUCTIVE PERFORMANCE OF STARTER GROWER FINISHER PHASE CROSS BREED PIGS THROUGH SUPPLEMENTATION OF ESSENTIAL AMINO ACID AND CHOLINE IN FEED - SUMARDANI N. L. G.; I K. SUMADI; I P. A. ASTAWA; N. M. WITARIADI (Majalah Ilmiah Peternakan)
Good reproductive performance can guarantee an increase in the pig population through the litter size and ser- vice per conception in a year. One factor that influences reproductive performance is feed containing amino acids. This research was carried out with the aim of determining the development of the reproductive organs of cross bre- ed pigs in the starter grower finisher phase through supplementation of essential amino acids (lysine, methionine, and tryptophan) and choline in the feed. This study used a completely randomized design (CRD) with 4 treatments and 3 replications, with a total of 12 weaned female pigs. Treatments in this study include P0: standard feed without a mixture of essential Amino Acids and Choline (AAC mixture); P1: P0 feed added 5% AAC; P2: P0 feed added 10% AAC; and P3: Po feed added 15% AAC. Data collection was carried out every 4 weeks for a6 weeks. The variable observed were the morphometry of the reproductive tract including the ovaries and follicles, oviducts, uterus and cervix. The data obtained were analyzed using analysis of variance, if there were significant differences (P<0.05), then continued with Duncan’s New Multiples Range Test analysis. The research results showed significant differen- ces (P<0.05) in all treatments for the observed variables, and treatments P2 showed the best results. The conclusion of this research is that the reproductive performance of cross breed pigs given 10% AAC mixture in their feed shows better development of reproductive organs.